The Effect of Spontaneous LH Surges on Pregnancy Outcomes in Patients Undergoing Letrozole-HMG IUI: A Retrospective Analysis of 6,285 Cycles - Jiang, Shutian; Chen, Li; Gao, Yining; Xi, Qianwen; Li, Wenzhi; Zhao, Xinxi; Kuang, Yanping (Frontiers in Endocrinology, 2022)
Background To date, no consensus has been reached on whether to wait for spontaneous luteinizing hormone (LH) surge to occur or to trigger ovulation regardless of the presence of an LH surge for achieving higher success rate in intrauterine insemination (IUI) cycles. Therefore, we hope to investigate the effect of the presence of a spontaneous LH surge on pregnancy outcomes in letrozole–human menopausal gonadotropin (LE-HMG) IUI cycles. Methods In this retrospective cohort study, a total of 6,285 LE-HMG IUI cycles were included between January 2010 and May 2021. Cycles were categorized into three groups: the trigger + LH surge group, the trigger only group, and the LH surge only group. The primary outcome measure was the clinical pregnancy rate. A logistic regression analysis was performed to explore other risk factors affecting the clinical pregnancy rate. Results No significant differences were observed in biochemical pregnancy rate (P =0.640), clinical pregnancy rate (P =0.702), ongoing pregnancy rate (P =0.842), and live birth rate (P =0.951) among the three groups. The binary logistic regression analysis also confirmed that the existence of an LH surge was not associated with clinical pregnancy. There was a difference in ectopic pregnancy rates (P =0.045), but logistic regression showed that the presence of a spontaneous LH surge has no association with ectopic pregnancy. Nonetheless, patients with lead follicles within 18.1-20.0 mm/20.1-22.0 mm and a long duration of LE treatment were less likely to get ectopic pregnant compared with patients with 14.1-16.0 mm lead follicles and shorter LE treatment (OR: 0.142, 95% CI: 0.023–0.891, P =0.037; OR: 0.142, 95% CI: 0.022–0.903, P =0.039; OR: 0.445, 95% CI: 0.235–0.840, P = 0.013). Conclusions The presence of a spontaneous LH surge in triggered LE-HMG IUI cycles does not appear to improve pregnancy rates. Thus, we suggest that waiting for an LH surge to occur is not necessary in triggered LE-HMG IUI cycles.